Psychometric Analysis of Validity and Reliability of The Indonesian Version of The Modified Fatigue Impact Scale in Chronic Disease Patients - Rostini, Heny; Sofiani, Yani; Rayasari, Fitrian; Azzam, Rohman; Astuti, Widya (Poltekkes Kemenkes Jakarta III, 2024)
Fatigue is a lack of physical or mental energy that can be felt by individuals and can disrupt daily activities. Fatigue causes a constant decrease in vitality, a lack of energy, and prevents sleep gaps from being filled, ultimately leading to a decline in productivity and quality of life. The prevalence of fatigue in chronic patients varies, as there is no specific data available. However, the prevalence of fatigue depends on the chronic disease in question, such as chronic kidney disease, diabetes mellitus, and heart disease. To obtain a valid and reliable Indonesian version of the MFIS instrument that can measure fatigue in patients with chronic diseases. The sampling technique used was based on the population, using a non-probability sampling method with purposive sampling. The population in this study consisted of patients with chronic diseases (Diabetes Mellitus, Congestive Heart Failure, Stroke). The population was 244 respondents (4 respondents for language comprehension, 30 respondents for validity and reliability testing, and 210 respondents for the final instrument test). The validity test results, with a sample of (n=210 respondents), showed a loading factor value greater than 0.135, indicating that all MFIS items were valid and highly correlated. The reliability test (n=210 respondents) yielded a Cronbach’s Alpha coefficient of 0.869. This study demonstrates that the Indonesian version of the MFIS instrument is valid and highly correlated. This instrument can be used to identify fatigue in chronic diseases and can serve as a guideline for nurses to implement fatigue interventions, thus helping to reduce and address fatigue issues in patients with chronic diseases.